The United Kingdom withdrawal procedure from the European Union - Soares, António Goucha (2022)
This article is about the United Kingdom’s withdrawal procedure from the European Union, in the aftermath of the Brexit referendum. It analyses the action of the political institutions involved in the withdrawal agreement negotiations, in particular, the constitutional dispute about the exit deal between the UK Government and the Parliament, as well as the way the European Union acted in the course of the whole procedure. Special attention will be given to the decisions delivered by the UK Supreme Court and by the European Court of Justice regarding the withdrawal procedure. The article aims to offer a new perspective, different from the prevailing accounts on the United Kingdom withdrawal negotiations, one that is based on a critical analysis of the attitudes of the main actors in the exit agreement, trying to apprehend their interaction during the whole process.